2022
DOI: 10.3390/app12136820
|View full text |Cite
|
Sign up to set email alerts
|

The Trends and Content of Research Related to the Sustainable Development Goals: A Systemic Review

Abstract: This study employed a comprehensive systematic review of the literature (SRL) process with the Content Analysis Toolkits for Academic Research (CATAR) for conducting a bibliometric analysis of the 2814 general SDG-related papers and 92 review papers selected from the Web of Science database from 2013 to 2022. The overview analysis found that the US and UK took the lead in publication and citation. The WHO and several universities were identified as the most prominent institutes around the globe. The field dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 95 publications
2
10
1
1
Order By: Relevance
“…Thus, it is noted that even though the total number of documents, TC, h-index, and IF indicate that SDG 3 is among the top 3 most relevant sources, the normalized citation data indicate that journals research on energy, multidisciplinary and general environmental sciences, and sustainability are among the most noticeable sources. It is important to highlight that this result is contrary to that obtained in bibliometric studies reported previously (Meschede 2020 ; Yeh et al 2022 ). This indicates that the number of citations alone is not adequate to assess the relevance of a document or journal (Simko 2015 ).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, it is noted that even though the total number of documents, TC, h-index, and IF indicate that SDG 3 is among the top 3 most relevant sources, the normalized citation data indicate that journals research on energy, multidisciplinary and general environmental sciences, and sustainability are among the most noticeable sources. It is important to highlight that this result is contrary to that obtained in bibliometric studies reported previously (Meschede 2020 ; Yeh et al 2022 ). This indicates that the number of citations alone is not adequate to assess the relevance of a document or journal (Simko 2015 ).…”
Section: Resultscontrasting
confidence: 99%
“…Although many bibliometric studies have been found in the field of SDGs research, most of them focus on specific disciplines, such as SDG and the business sector (Pizzi et al 2020), education (Prieto-Jiménez et al 2021, poverty (Yu and Huang 2021), and few bibliometric studies cover the SDG general aspects and its evolution. Nevertheless, some interesting bibliometric studies of SDG trends are worth mentioning, such as the study of Díaz-López et al (2021), Meschede (2020), Yeh et al (2022), andSianes et al (2022). All of them included a large number of documents (thousands) and do none of them focused on literature review articles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of SDGs in the food industry to achieve sustainable change and improve social and environmental well-being has been the subject of research (Yeh et al ., 2022). Green knowledge management strengthens organisational capabilities for firms to achieve green innovation (Wong et al ., 2022) and the SDGs (Wang et al ., 2022).…”
Section: Literature Review: Sdgs In the Food Sectormentioning
confidence: 99%
“…El número de publicaciones científicas sigue en aumento; las temáticas de interés mundial como la sostenibilidad no son la excepción entre los temas tratados. Como ejemplo, los documentos que abordan los Objetivos de Desarrollo Sostenible (en la base de datos Web of Science) pasó de siete a 774 entre los años 2013 y 2021 (Yeh et al, 2022). Todo ello es solo una pequeña muestra del esfuerzo de la comunidad científica por dar a conocer sus hallazgos y relacionarlos con temáticas de interés público.…”
unclassified